45 ROLE OF GALECTINE-3 AND ST-2 IN THE CHARACTERIZATION OF MYOCARDIAL INVOLVEMENT IN PATIENTS WITH TRANSFUSION DEPENDENT BETA THALASSEMIA. (15th December 2022) - Monitillo, Francesco; Dadamo, Michele; Santoro, Daniela; Basile, Paolo; Vitucci, Angelantonio; Del Vecchio, Giovanni Carlo; Di Gennaro, Daniela; Zucano, Stefania; Giordano, Paola; Guaricci, Andrea Igoren; Ciccone, Marco Matteo
Abstract: Rationale and Aim of the Study: Cardiac involvement is very common in transfusion dependent beta-thalassemia (TDT) and is mainly related to cardiac iron overload and myocardial damage with progressive systolic and diastolic dysfunction of the left and right ventricles. It has also been observed that in patients with TDT, cardiac fibrosis may not be directly related with iron deposition and is associated with a higher risk of cardiovascular complications. CMR is the gold standard for the evaluation of iron overload with T2* sequences and for the detection of cardiac fibrosis with late gadolinium enhancement (LGE) Apart from the use of imaging techniques, it is well known that the fibrosis and inflammation biomarkers, Galectin-3 (Gal-3) and ST2, are involved in the early stages and progression of various fibrosis-related diseases, such as heart failure, liver cirrhosis, renal and pulmonary fibrosis. To date, the role of Gal-3 and ST-2 as markers of cardiac fibrosis and myocardial damage and their possible association with myocardial damage detected by CMR, has never been studied in patients with TDT. The aim of the study was to evaluate the role of Gal-3 and ST-2 in the characterization of myocardial involvement, especially cardiac fibrosis in a population of TDT patients. Methods: Twenty-six patients with a confirmed diagnosis of TDT, based on βglobin genotype, transfusion history and clinical evaluation, undergoing periodic blood transfusion and iron-chelation therapy were enrolled. None presented overt clinical signs of heart failure, CMR with T2* technique, haematochemical routine, ferritinemia assay, Gal-3 and ST-2 assay and dynamic ECG Holter were performed on all patients. Results: Both Gal-3 and ST-2 have a positive correlation with systemic markers of inflammation, such as erythrocyte sedimentation rate (ESR) (10 0.65 p 0.042 and 26 0.58 p 0.002, respectively). A Gal-3 value > 17.9 ng/mL is associated with inflammatory comorbidities such as diabetes (p 0.010) and with cardiac iron overload evaluated using CMR T2 * technique (p 0.007) (Fig.1). A positive correlation was also observed with medium values of ferritine (rho 0.46 p 0.017). There was a statistically significant positive association between an ST-2 value > 35 ng/mL and cardiac fibrosis detected by CMR (p 0.020) (Fig. 2). Higher ST-2 values have been detected in patients with cardiac fibrosis when compared to those without (42 ± 14 vs 28 ±8 p 0.006). Conclusions: The present study demonstrates that, in a small population of TDT patients undergoing periodic blood transfusion and iron-chelation therapy with no overt clinical signs of heart failure, Gal-3 appears to be a marker of cardiac iron overload detected with CMR T2* sequences and systemic inflammation associated with higher ESR values and inflammatory comorbidities such as diabetes mellitus. ST-2 is a marker of cardiac fibrosis detected by CMR LGE.